The Problems Encountered by Male and Female Students in Learning Speaking Skill - Muhammad Naufal; Asnawi Muslem; Endang Komariah (Research in English and Education Journal, 2017)
The purpose of this study is to investigate the problems faced by male and female students in learning speaking skill which are related with the components in speaking and the factors that cause difficulties in speaking. This study took place in SMP negeri 1 Banda Aceh. The sample in this study was 80 of second grade students (40 for male and 40 for female students). In order to ascertain the problems faced by students in learning this skill, qualitative study design undertaken by using purposive sampling. To collect the data in this study, the researcher used the questionnaire items as a main of instrument in collecting data. To strengthen the result of questionnaire, the researcher asked 4 questions in interview guide to the students in relation to the problems of speaking. The collected data were analyzed by presenting them in the form of narration and following three steps proposed by Miles and Huberman (as cited in Sugiyono, 2012). The research finding shows that all students face problems in speaking. According from male and female students, the most problems that they faced in learning speaking skill were lack of vocabulary, poor pronunciation, not fluent to speak, afraid of making errors while speaking, less confidence to speak, nervous to speak, not accustomed to speaking English, difficult to express words and sentences and accustomed using of native language in daily conversation.